(untitled) (The Pakistan Development Review, 2011)
This paper examines whether trade liberalisation played a role in shaping the wage structure of Pakistan in the late 1990s and early 2000. It uses manufacturing workers data from LFS supplemented by external information to analyse the impact of trade liberalisation. In general, the results show that trade liberalisation, measured through import penetration ratio, export penetration ratio and relative prices of each industry, not only impacted wages but also increased wage inequality across skill levels from 1996-97 to 2005-06. The econometrics analysis confirms that increase in import penetration raises skilled premium while simultaneously reducing unskilled premium; a result in contention with the findings of the Stolper-Sameulson Theorem.